2021
DOI: 10.1021/acsenergylett.1c00972
|View full text |Cite
|
Sign up to set email alerts
|

Realistic Efficiency Limits for Singlet-Fission Silicon Solar Cells

Abstract: Singlet fission is a carrier multiplication mechanism that could make silicon solar cells much more efficient. The singlet-fission process splits one high-energy spin-singlet exciton into two lower-energy spin-triplet excitons. We calculated the efficiency potential of three technologically relevant singlet-fission silicon solar cell implementations. We assume realistic but optimistic parameters for the singlet-fission material and investigate the effect of singlet energy and entropic gain. If the transfer of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…Using this database of excitation energies, the suitability of each candidate structure for SF-PV was assessed based on two factors: (a) whether the predicted singlet excitation energy was within the range of twice the predicted triplet excitation energy (i.e. |E(S 1 ) − 2E(T 1 )| < 0.03 eV allowing only for slightly exoergic candidates); and (b), whether the predicted triplet excitation energy E(T 1 ) was larger than the band gap energy of silicon (1.12 eV 29 ) to avoid voltage penalties in hypothetical devices 21 . We found that 30.15% of the 2,2′-diethenyl subspace fulfilled the SF condition (a), and 8.82% of the overall chemical space also fulfilled the photovoltaic condition (b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this database of excitation energies, the suitability of each candidate structure for SF-PV was assessed based on two factors: (a) whether the predicted singlet excitation energy was within the range of twice the predicted triplet excitation energy (i.e. |E(S 1 ) − 2E(T 1 )| < 0.03 eV allowing only for slightly exoergic candidates); and (b), whether the predicted triplet excitation energy E(T 1 ) was larger than the band gap energy of silicon (1.12 eV 29 ) to avoid voltage penalties in hypothetical devices 21 . We found that 30.15% of the 2,2′-diethenyl subspace fulfilled the SF condition (a), and 8.82% of the overall chemical space also fulfilled the photovoltaic condition (b).…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, when the energy of the decoupled T 1 states are high enough, both triplet excitons can be used to drive a photovoltaic current 20 . Note, that while triplet excitons with energies below the PV semiconductor's band-gap are also generally available for this process, the occurrence of dark recombination currents can lead to a voltage penalty in that case 21 . Finally, when more than one exciton per photon can be made available as charge carriers the device formally exceeds the SQ limit.…”
Section: Introductionmentioning
confidence: 99%
“…CT is accompanied by exciton dissociation into free electrons and holes in the presence of the staggered band offsets at the heterointerface with counterpart organic or inorganic semiconductors (downward and upward for electrons and holes, respectively), followed by the independent transport of the free carriers (Figure 3a). [22] In other words, the energy band alignment between two constituent semiconductors Photovoltaic responses from the p-n photodiodes equipped with different thicknesses of TMDs. Reproduced with permission.…”
Section: Singlet Fission Solar Cells: Working Mechanisms and Examplesmentioning
confidence: 99%
“…Charge transfer (CT) and Dexter energy transfer (DET) have been suggested as pathways that could explain the direct triplet transfer. CT is accompanied by exciton dissociation into free electrons and holes in the presence of the staggered band offsets at the heterointerface with counterpart organic or inorganic semiconductors (downward and upward for electrons and holes, respectively), followed by the independent transport of the free carriers (Figure 3a) [22] . In other words, the energy band alignment between two constituent semiconductors determines the migration of both or either of the charge carriers (electrons and holes).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation